Evaluation of maize distillers dried grains with solubles in the feeding of White Leghorn L-33 laying hens - Rodríguez, Bárbara; Vázquez, Ysnagmy; Valdivié, Manuel; Herrera, Magalys (Cuban Journal of Agricultural Science, 2017)
For determining the effect of maize dried distillers grains with solubles on egg production and yolk color, a total of 270 White Leghorn L-33 laying hens was used. Animals were randomly distributed in three feeding treatments: inclusion of 0 (control diet), 10 and 20 % of distillers dried grains with 10 replications and 9 fowls per replication during 20 laying weeks (24 to 44 weeks). The inclusion of distillers dried grains in the diet did not affect egg production, egg weight and mass conversion. However, there was an increase in feed conversion with 10 % (P < 0.05). Yolk color was more intense with the inclusion of distillers dried grains and 20 % was superior to 10 %. Results suggest the possibility of adding up to 20 % in the laying hen diets without negative effect on egg production. Further studies are necessary related to the internal and external egg quality, as well as on the economic benefits of this by-product on substituting raw matters of higher costs (soybean and calcium phosphate). Key words: non-conventional feeds, agro-industrial by-byproducts, laying hens, DDGS